CO2 oxidation of carbon nanotubes for lithium-sulfur batteries with improved electrochemical performance. (June 2018) - Wang, Datao; Wang, Ke; Wu, Hengcai; Luo, Yufeng; Sun, Li; Zhao, Yuxing; Wang, Jing; Jia, Lujie; Jiang, Kaili; Li, Qunqing; Fan, Shoushan; Wang, Jiaping
Abstract: The fabrication of high-performance cathodes with high sulfur content is essential for the practical realization of lithium–sulfur (Li–S) systems. The preparation of high-sulfur-content electrodes is currently hindered by poor dispersion of the conductive agents; nonuniformly distributed conductive agents cannot provide sufficient sulfur-loading sites, thereby resulting in aggregation of sulfur/Li2 S and severe polarization. To deal with this issue, we prepare CO2 modified carbon nanotube (CNT)-based cathodes for Li–S batteries. CNTs are exposed to CO2 at 900 °C, resulting in uniformly distributed negative charges on the external surface of the tubes; the electrostatic repulsion facilitated the dispersion of CNTs. Compared with the previous work on CNTs prepared by air oxidation (denoted as air-CNTs), the dispersions of the CO2 -treated CNTs (denoted as CO2 -CNTs) are more stable, which allows higher sulfur loading and improves sulfur utilization. A free-standing CO2 -CNT&S electrode with a sulfur content of 80 wt% is fabricated through a sonication-assisted method. The excellent dispersion of the CO2 -CNT&S network results in little kinetic barriers, low polarization, and fast charge transport at the interface of the electrode and electrolyte. The CO2 -CNT&S electrode delivers a lower capacity fading rate and superior rate performance compared with the air-CNT&S electrode. Graphical abstract: Image 1